The meeting of Bill and Bob: Helping the cause of countless alcoholics - Nishtha Chawla (Journal of Mental Health and Human Behaviour, 2017)
The concept of “Alcoholics Anonymous” (AA) is familiar to mental health professionals and the general populace. The premise of the organization lies in individual suffering from problems related to alcohol embarking on a journey to submit before the almighty, taking cognizance of the effects caused by alcohol, making amends in life to people who have been harmed and taking action to prevent relapse to alcohol. The AA was formed after a fortuitous meeting of Bill Wilson and Dr. Bob Smith in Ohio. The duo subsequently embarked on the journey of helping others with alcohol-related problems. Since then, AA has grown gradually and how has more than 2 million members in its fold. This write-up traces the events that led to the meeting of Bill and Bob and the formation of AA, which led to a significant impact on individuals with alcohol use problems.